Mutsu Munemitsu and his time - Okazaki, Hisahiko 1930-2014 (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan))
"Toward the end of the Tokugawa shogunate, Mutsu Munemitsu was ousted from his home Kish?u-han as a result of his father's defeat in a power struggle. To avenge this, Mutsu bolstered his talent to become a man of "genius and learning in equal measure." He joined the Kobe Naval Training Center founded by Katsu Kaish?u and, later, Kaientai, a trading and shipping company and private navy founded and managed by Sakamoto Ry?oma before the Meiji Restoration was accomplished. During the Meiji era, Mutsu fully exercised his extraordinary ability, including working to revise unequal treaties with Western powers as foreign minister. In his last days, he scrambled to end the First Sino-Japanese War; his efforts resulted in the signing of the Treaty of Shimonoseki with favorable terms for Japan. Mutsu also helped Japan ride out the subsequent wave of the Tripartite Intervention from Russia, France, and Germany. This book's author, a career diplomat himself, traces the footsteps of modern Japan's diplomacy by reviewing the philosophical and political journey of this extraordinary diplomat who protected the dignity of Japan as a modern nation throughout his professional life" --United summary from book.